Spectators in Olympic sport - Digel, H. (New Studies in Athletics, 2009)
Without spectators, modern top-level sport is inconceivable. However, despite their significance, they are a phenomenon about which little is known. The author attended competitions of more than half the sports at the 2008 Olympic Games in Beijing. Drawing on this experience, he finds that spectators at the gymnastics finals or in the athletics stadium or at team handball matches are by no means uniform. Rather, they display a wide variety of features. Some of these define a type of spectator seen across many sports, such as those who attend voluntarily, VIPs and invited guests, and students and military who are forced to fill seats and given equipment to make noise. Other groups are distinguished by their biased or impartial behaviour towards the performers. Other groups discussed are those that are significant as individual features for a specific sport. Mentioning some negative trends that can be observed in modern spectators, he concludes that further research would be worthwhile. Sport organisers, including international federations and the International Olympic Committee, have a responsibility and an interest in this area. They must first better understand spectator attitudes and behaviour and then develop them in a way that benefits their sports and society as a whole.